UPAYA PEMBERDAYAAN PENINGKATAN RUMAH SEHAT DI DUSUN PRINGGOLAYAN KECAMATAN BANGUNTAPAN TAHUN 2020 - Maulana, Muchsin; Yuliana, Deta; Listari, Irma; Fadhila, Nurul; Aulia, Ranissa; Rahma, Syfa Alifah; Hestiyani, Teti (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2020)
The house is a basic human need to live and as a means of interaction between fellow residents and even the environment. Community life of RT 04 and 07 Pringgolayan village are still very simple. So that it affects the awareness of environmental health, especially in managing and maintaining the hygiene of each resident's home. There are still many houses that do not open windows every day and there are wigglers in the bathtub. Therefore, further education is needed at the family level on how to keep the house healthy. The purpose of this activity is to provide education about the efforts that can be made to improve healthy homes. The method used is through counseling about efforts to improve healthy homes and by distributing leaflets to each resident's home. The target are PKK women RT 04 and 07 Pringgolayan village. When the activity is carried out, mothers can actively participate and capture the education that has been delivered. The impact obtained is that PKK women can increase knowledge and increase awareness to make their homes healthy.